Cardiotrophin-1 determines liver engraftment of syngenic colon carcinoma cells through an immune system-mediated mechanism - Bustos, Matilde (Landes Bioscience, 2012)
Cardiotrophin-1 (CT-1/CTF1) is a member of the interleukin-6 (IL-6) family of cytokines that stimulates STAT-3 phosphorylation in cells bearing the cognate receptor. We report that Ctf1(−/−) mice (hereby referred to as CT-1(−/−) mice) are resistant to the hepatic engraftment of MC38 colon carcinoma cells, while these cells engraft normally in the mouse subcutaneous tissue. Tumor intake in the liver could be enhanced by the systemic delivery of a recombinant adenovirus encoding CT-1, which also partly rescued the resistance of CT-1(−/−) mice to the hepatic engraftment of MC38 cells. Moreover, systemic treatment of wild-type (WT) mice with a novel antibody-neutralizing mouse CT-1 also reduced engraftment of this model. Conversely, experiments with Panc02 pancreatic cancer and B16-OVA melanoma cells in CT-1(−/−) mice revealed rates of hepatic engraftment similar to those observed in WT mice. The mechanism whereby CT-1 renders the liver permissive for MC38 metastasis involves T lymphocytes and natural killer (NK) cells, as shown by selective depletion experiments and in genetically deficient mice. However, no obvious changes in the number or cell killing capacity of liver lymphocytes in CT-1(−/−) animals could be substantiated. These findings demonstrate that the seed and soil concept to understand metastasis can be locally influenced by cytokines as well as by the cellular immune system.